Design and efficiency assessment of a passive treatment system for acid mine drainage - Ruiwen YAN; Jun ZHU; Junhao ZHU; Gang LIN; Wanqiu ZHANG; Zenghua JIA; Wenming WANG; Furui XI (Meitian dizhi yu kantan)
BackgroundAcid mine drainage (AMD) refers to highly acidic, heavy metal-rich effluent generated from mining activities, potentially causing severe environmental contamination. Methods Focusing on the Lujiang alum mine in Anhui Province, this study established a systematic framework for the design and assessment of an integrated passive AMD treatment system using the Phreeqc and AMDTreat software. Based on a comprehensive analysis of the on-site hydrogeochemical characteristics (pH: 2.93‒3.06, Fe: 5.98‒42.52 mg/L, and Al: 18.87‒32.14 mg/L) and physical conditions (flow rate: 50‒96 m3/h, available area: about 50 000 m2), this study proposed a hybrid passive treatment system comprising a vertical flow wetland and a following aerobic artificial wetland. Finally, this study predicted the performance of the system using a Phreeqc-based hydrogeochemical model. Results and Conclusions The results indicate that the integrated passive treatment system could effectively increase the effluent pH to approximately 7.6 and yield high removal rates of above 99.0% for Fe and Al and above 97.0% for other heavy metals like Cu. Accordingly, the effluent quality after treatment satisfied the criteria for class III water specified in Chinese standard Environmental Quality Standards for Surface Water (GB 3838—2002). The life-cycle cost analysis performed using AMDTreat indicates that the construction costs and annual operation and maintenance (O&M) costs of the proposed system were approximately 3.68 million yuan and 0.46 million yuan, respectively. Therefore, this system enjoys significant long-term cost advantages over traditional active treatment technologies. The proposed design method that integrates technology selection, efficiency simulation, and economic assessment not only suits the AMD treatment of the Lujiang alum mine but also provides a scientific basis and technical reference for ecological restoration of similar mining areas.